Электромеханические процессы в линейном импульсно-индукционном электромеханическом преобразователе с подвижным индуктором и двумя якорями - Болюх, Владимир Федорович; Кочерга, Александр Иванович; Щукин, Игорь Сергеевич (НТУ "ХПИ", 2018)
Разработана математическую модель, которая описывает электромеханические процессы в линейном импульсно-индукционном электромеханическом преобразователе с подвижным индуктором, взаимодействующим со стационарным якорем (СЯ) и подвижным якорем (ПЯ), ускоряющим исполнительный элемент. Установлено влияние высот якорей на электромеханические процессы в преобразователе. Если высота СЯ в два раза больше высоты ПЯ, то на индуктор в начальный момент времени действуют электродинамические усилия (ЭДУ), прижимающие его к СЯ и перемещение индуктора начинается с задержкой 0,35 мс. Если высота ПЯ в два раза больше высоты СЯ, то на индуктор в начальный момент времени действуют ЭДУ, отталкивающие его от СЯ, и его перемещение начинается с задержкой 0,1 мс. Если высоты СЯ и ПЯ равны, то до момента времени 0,15 мс на индуктор практически не действуют ЭДУ и перемещение индуктора начинается с задержкой 0,25 мс. Установлены комбинации геометрических параметров якорей, при которых действуют как наибольшие, так и наименьшие импульсы ЭДУ. Наибольшие скорости развивает наиболее низкий ПЯ, причем высота СЯ на них практически не влияет. С увеличением массы исполнительного элемента происходит увеличение токов в активных элементах преобразователя и уменьшение скоростей индуктора и ПЯ. При этом максимальные значения ЭДУ, действующих на индуктор, уменьшаются, а на якоря – увеличиваются.

The purpose of the paper is to determine the influence of the height of the mobile and stationary disk electrically conductive armatures covering the movable inductor on the electromechanical processes of linear pulsed-induction electromechanical converter (LPIEC). With the help of the developed mathematical model that describes electromechanical and thermal processes of LPIEC, the influence of the heights of the armatures on electro-mechanical processes, the values of the electrodynamic forces acting on the inductor and armature, and the moving speed of the movable armature (MA) is established. It is shown that if the height of the stationary armature (SA) is twice the height of the MA, then the inductor at the initial instant of time is acted upon by electrodynamics forces pressing it to the SA, and the displacement of the inductor begins with a delay of 0.35 ms. If the height of the MA is twice the height of the SA, then the electrodynamics forces act on the inductor at the initial instant of time, repelling it from the SA, and its movement begins with a delay of 0.1 ms. If the heights of the SA and the MA are equal, then until the time 0.15 ms on the inductor, the electrodynamics forces practically do not act and the inductor moving relative to the SA begins with a delay of 0.25 ms. The effect of the geometric parameters of the SA and MA on the velocity of the inductor moving relative to the SA, MA relative to the inductor and the MA relative to the SA is established. It has been established that the highest velocity of the MA relative to the SA develops the lowest MA, and the height of the SA does not affect it practically. However, with the increase in the height of the MA, the effect of SA begins to affect. In this case, it is expedient to select the height of the SA to be 0.4-0.42 of the height of the inductor. It is shown that as the weight of the actuating element increases, the currents in the active elements of the LPIEC increase, the induction velocities of the inductor relative to the SA and the MA decrease relative to the inductor. At the same time, the maximum the electrodynamic forces values acting on the inductor decrease, and the armatures increase. Moreover, the maximum the electrodynamic forces acting on the MA are less than similar forces acting on the SA.
Electromechanical processes in a linear pulse-induction electromechanical converter with a movable inductor and two armatures
Keywords: математическая модель; стационарный якорь; подвижный якорь; ПЯ; СЯ; электродинамические усилия; емкостный накопитель энергии; ЕНЭ; mathematical model; mobile inductor; stationary armature